Coincidence of Rhinoscleroma and Rosai-Dorfman disease (Sinus histiocytosis with massive lymphadenopathy): Report of a case - Naraghi M; Madani SZ; Kashfi A (Acta Medica Iranica, 2002)
A 35-year-old man was admitted because of a 2-year history of nasal obstrction, a nasopharyngeal mass, malaise, and massive cervical lymphadenopathy. Nasal symptoms and nasopharygeal mass were due to rhinoscleroma that was confirmed by an incisional biopsy and culture. The patient underwent cervical lymph node biopsy and culture. The patient underwent cervical lymph node biopsy that revealed the tissue compatible with Rosai-Dorfman disease, also called sinus histiocytosis with massive lymphadenopathy. Rhinoscleroma was treated by a combination of excision and antibiotics. Culture became negative for Klebsiella rhinoscleromatis. Then prednisolone administered for one month and gradually tapered. Lymph nodes became small at the end of treatment. Twelve months follow-up showed no evidence of recurrence of both diseases. To the best of our knowledge, this is the first report of association of rhinoscleroma with Rosai-Dorfman disease. Association of these two rare diseases may be due to just a coincidence, or a common immunologic or microbiologic underlying factor